A Research on The Relation between the Healthy Life Style Behaviors and Self-Care Levels of the Students in Health and Social Programs of Vocational Collages (Annals of Medical Research, 2021)
None
Keywords: Students at vocational collages, Healthy-Life-Style Behaviors, Self-care agencyemife/em